Development of novel molecular probes to study cellular behaviour using NMR: - Kishigami, S (2023)

(untitled)
This DPhil thesis describes the novel analytical methodologies developed by the author using biomolecular Nuclear Magnetic Resonance (NMR) spectroscopy. These new bio-NMR methods address the current limitations in modern NMR spectroscopy and can be used to study the structure and dynamics of target biomolecules in complex cellular environments. More specifically, the author synthesised small molecules labelled with stable isotopes which are NMR active and can be used for molecular biology experiments to gain useful biological insights. Chapter 1 clarifies the strengths and weaknesses of the modern NMR methodologies and describes the research backgrounds of the DPhil research projects. Then, Chapter 2 describes a 15N isotope labelling technique and a heteronuclear NMR method to detect the cellular uptake of a potent drug candidate by the mammalian cells. In Chapter 3, the motivation for the development of a novel (13CF3) NMR probe is explained with the synthetic procedures to prepare the molecules labelled with the (13CF3) moieties. Chapter 4 provides a detailed explanation of a molecular biology methodology to deliver the unnatural (13CF3) label to proteins of interest. The NMR results obtained from the (13CF3)-labelled Hsp 16.5 protein sample in Chapter 5 confirmed a significant potential of the (13CF3)-group to study structures and dynamics of high molecular weight biomacromolecules. A unique application of the fluorine NMR probe to label spider silk protein fibre is introduced in Chapter 6. The conclusions and outlook of the work described in this DPhil thesis are presented in Chapter 7. Overall, this DPhil thesis aims to provide some unique NMR methodologies for studying the behaviour of biomolecules in complex cellular contexts and contribute to the understanding of biological phenomena by using these NMR techniques.